Clinical Characteristics and Optimization of Empirical Antimicrobial Therapy for Febrile Neutropenia in Patients With Hematologic Malignancies - Cui Y; Liu X; Feng S (Infection and Drug Resistance)
Yuqing Cui,1,2 Xin Liu,1,2 Sizhou Feng1,2 1State Key Laboratory of Experimental Hematology, National Clinical Research Center for Blood Diseases, Haihe Laboratory of Cell Ecosystem, Institute of Hematology & Blood Diseases Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, Tianjin, 300020, People’s Republic of China; 2Tianjin Institutes of Health Science, Tianjin, 300020, People’s Republic of ChinaCorrespondence: Sizhou Feng, Email doctor_szhfeng@163.comPurpose: Since the publication of the 2011 Infectious Diseases Society of America (IDSA) guidelines for empirical treatment of febrile neutropenia (FN), there have been significant shifts in pathogen profiles and emerging challenges in treatment. These include increased prevalence of multidrug-resistant (MDR) bacteria and changes in the distribution of Gram-negative or Gram-positive bacteria (GPB). The study aims to update and optimize empirical treatment strategies for hematological malignancy (HM) patients, a population particularly vulnerable to these evolving threats.Methods: A literature review was conducted on studies published between January 2010 and December 2023 regarding empirical treatment of FN in HM patients, focusing on pathogen characteristics, treatment regimens, and duration of therapy.Results: Approximately one-third of HM patients with FN experience fever of unknown origin (FUO), while 40– 50% have clinically documented infections (CDI), and 10– 30% present with microbiologically documented infections (MDI), with a predominance of Gram-negative bacteria (GNB). Factors such as prolonged neutropenia, prior broad-spectrum antibiotic use, and previous infections with drug-resistant bacteria are associated with MDR infections. Cefepime, piperacillin/tazobactam (PTZ), and carbapenem are viable empirical treatments for high-risk HM patients, though cefepime monotherapy’s advantage remains uncertain. In cases of pneumonia, shock, or suspected carbapenem-resistant infections, combination therapy, tigecycline, and newer antibiotics like ceftazidime/avibactam (CAZ/AVI) are often used. Empirical broad-spectrum antibiotics can be safely discontinued in FUO patients after 48 hours of clinical stability and apyrexia.Conclusion: Proper selection of empirical antibiotics and determining optimal treatment duration are essential for reducing antibiotic resistance and improving outcomes in HM patients with FN. These findings underscore the need for updated clinical guidelines that address evolving pathogen profiles and the growing challenge of MDR infections.Summary: Infection-related complications remain a leading cause of mortality in HM patients, often limiting the implementation of chemotherapy. Early and appropriate empirical therapy significantly improves outcomes in FN, reducing hospital stays and healthcare costs. Effective treatment strategies require careful evaluation of local microbial epidemiology, risk factors for drug resistance, and predictors of poor prognosis. For high-risk FN patients, first-line antibiotic options include cefepime, PTZ, and carbapenems. In cases of pneumonia, septic shock, or suspected carbapenem-resistant infections, combination therapies with antipseudomonal β-lactams, aminoglycosides, or novel agents like CAZ/AVI are recommended. In patients with FUO, discontinuing broad-spectrum antibiotics may be considered 48 hours after defervescence in clinically stable patients, though premature cessation should be avoided for those with persistent fever. Ongoing monitoring and reassessment of the patient’s condition are crucial to minimizing the risks of treatment failure. Timely, evidence-based empirical therapy remains critical for improving outcomes in FN, and continued advancements in antimicrobial strategies are essential to optimizing care for this high-risk patient population.Keywords: hematological malignancy, febrile neutropenia, multidrug-resistant bacteria, empirical antibiotic treatment, fever of unknown origin